Infraorbital nerve block with 0.25% levobupivacaine on labioplasty procedure: Case Reports - Islam, Ahmad Nur (Hasanuddin University, 2022)
Labioplasty was a routine procedure performed by oral surgeons. The development of surgical techniques in this procedure has affected the full range of cosmetic healing. The combination of infraorbital nerve blocks with general anesthesia has been used to minimize post operative pain labioplasty procedures. The infraorbital nerve is a terminal branch in the second division of the trigeminal nerve, coming through the infraorbital foramen. Selection of blocks with an intraoral approach is because it is easy to use in everyday practices and effectively produces analgesia in the upper lip region. 5 patients undergoing labioplasty procedures between the September - October 2021 at Oral and Dental Teaching Hospital Hasanuddin University with GETA technique. Applied the infraorbital nerve block with an intraoral approach and injection of 1 ml 0.25% levobupivacaine each side. The infraorbital nerve block technique with intraoral approach using levobupivacain 0.25% providing a good perioperative analgesia on the labioplasty procedure. A good pain perioperative provides the advantage of a steady hemodynamic, facilitating ambulation, and fasten patient recovery.